Consumer Perception and the Evaluation to Adopt Augmented Reality in Furniture Retail Mobile Application - Muhamad Abdilah Ramdani; Prawira Fajarindra Belgiawan; Fitri Aprilianty; Mustika Sufiati Purwanegara (Bina Nusantara University, 2022)
The importance of retailers to utilize interactive technology, such as Augmented Reality (AR), in their mobile applications is considered due to the change in consumer behavior from in-store to online. However, there is limited study in understanding consumer perception to evaluate the effectiveness of AR implemented by retailers during the COVID-19 pandemic in developing countries like Indonesia. The research examined the relationship between AR characteristics, consumer perception, and attitude toward AR in mobile furniture retail applications. The intention to adopt was also included in measuring behavioral responses. Using 383 valid data, the researchers empirically tested the insights through Partial Least Square-Structural Equation Modelling (PLS-SEM). The results reveal that AR characteristics have a significant influence on consumer perception. Besides, perceived functional benefit and trust in AR directly relate to attitude toward AR and indirect on intention to adopt AR applications. Thus, the research provides managerial implications for retailers to adopt AR technology as interactive media to enhance customer experience during online shopping in the current and after the pandemic. It is also expected to help government regulation in digital infrastructure to support AR implementation in industry and users’ data privacy. In addition, the research contributes to theoretical development in AR adoption, interactive marketing, and consumer behavior.